The effect of obesity on revision rate in unicompartmental knee arthroplasty: a systematic review and meta-analysis - Musbahi, O; Hamilton, T; Crellin, A; Mellon, S; Kendrick, B; Murray, D (Springer, 2020)
The number of patients with knee osteoarthritis, the proportion that is obese and the number undergoing unicompartmental knee arthroplasty (UKA) are all increasing. The primary aim of this systematic review was to determine the effects of obesity on outcomes in UKA. A systematic review was performed using PRISMA guidelines and the primary outcome was revision rate per 100 observed component years, with a BMI of ≥ 30 used to define obesity. The MINORS criteria and OCEBM criteria were used to assess risk of bias and level of evidence, respectively. 9 studies were included in the analysis. In total there were 4621 knees that underwent UKA. The mean age in included studies was reported to be 63 years (mean range 59.5–72 years old)) and range of follow up was 2–18 years. Four studies were OCEBM level 2b and the average MINORS score was 13. The mean revision rate in obese patients (BMI > 30) was 0.33% pa (95% CI − 3.16 to 2.5) higher than in non-obese patients, however this was not statistically significant (p = 0.82). This meta-analysis concludes that there is no significant difference in outcomes between obese and non-obese patients undergoing UKA. There is currently no evidence that obesity should be considered a definite contraindication to UKA. Further studies are needed to increase the numbers in meta-analysis to explore activity levels, surgeon’s operative data, implant design and perioperative complications and revision in more depth.